SIKAP DAN PERSEPSI KONSUMEN TERHADAP KEPUTUSANPEMBELIAN ONLINE DI SUNGAI LILINMUSI BANYUASIN - Juairiah, Juairiah; Busono, Genot Agung; Fadeli, Deni (Universitas muhammadiyah palembang, 2017)
The formulation of the problem in this research is whether the influence ofconsumer perceptions and attitudes toward online purchasing decisions inSungai Lilin District Musi Banyuasin. The purpose of this study is todetermine the influence of consumer perceptions and attitudes toward onlinepurchasing decisions in Sungai Lilin District Musi Banyuasin. The method inthis research is using assosiatif method, assosiatif method that is researchproblem problem which is stated relationship two variable or more. Thelocation of this research is in Sungai Lilin District Musi Banyuasin. Thepopulation in this study is the community in Sungai Lilin District MusiBanyuasin. The sample in this research is 100 respondents by using clustersampling method, that is sampling based on wide area or geographicallocation and sampling randomly. The data required in this study using primarydata. The method of data collection is questionnaire. The data obtained wereanalyzed using multiple linear regression technique. The test results provethat the variables of perception and consumer attitudes together significantlyinfluence simultaneously to the purchase decision variables. Hypothesistesting partially proves that, consumer attitudes have a significant effect onpurchasing decisions. While the perception has no significant effect onpurchasing decisions.